2016
DOI: 10.1542/peds.2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assisted Endovascular Thrombolysis in Adolescents: 2 Case Reports

Abstract: Descending iliofemoral thrombosis in children is a rare event. Anticoagulation therapy with low-molecular-weight-heparin is standard of care. However, patency cannot be achieved in all cases, increasing the risk for rethrombosis and postthrombotic syndrome. To reduce the risk of venous valve failure in adults, local catheter-directed thrombolysis is used to reopen vessels. Two adolescent girls (17 and 15 years old) presented with acute descending iliofemoral thrombosis of the left common iliac, external, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Usually neonates and adolescents are affected and thrombosis is typically associated with the use of intravenous catheters or severe morbidities (sepsis, cancer, heart disease, etc.). Anatomic abnormalities, primarily aplasia of the inferior vena cava and May-Thurner syndrome, and/ or disturbances of the coagulation syndrome can also be of an importance [1][2][3][4][5][6][7]. Unprovoked thrombosis in a child, such as in our patient is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Usually neonates and adolescents are affected and thrombosis is typically associated with the use of intravenous catheters or severe morbidities (sepsis, cancer, heart disease, etc.). Anatomic abnormalities, primarily aplasia of the inferior vena cava and May-Thurner syndrome, and/ or disturbances of the coagulation syndrome can also be of an importance [1][2][3][4][5][6][7]. Unprovoked thrombosis in a child, such as in our patient is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…[121][122][123] Although no RCTs have assessed the safety and efficacy of this approach in pediatric patients, published data from retrospective studies and case reports have shown that the use of conventional anticoagulation, CDT, and stent placement results in high rates of recanalization and long-term patency of the iliac vein, with significant improvement in symptoms while potentially decreasing the development of PTS. 113,124,125 Surgical approaches, including thrombectomy of the iliofemoral veins with iliac venous reconstruction or placement of a cross-femoral venous bypass graft, are not recommended as first-line management, and are typically reserved for patients with significant contraindications to CDT, as they can result in high morbidity with variable rates of successful venous recanalization. 114,116 Conclusion VTE has become an increasingly recognized problem in pediatrics that can significantly impact the health outcomes of affected children.…”
Section: May-thurner Syndromementioning
confidence: 99%